Potential Use of Microbial Community Genomes in Various Dimensions of Agriculture Productivity and Its Management: A Review - Iquebal, Mir Asif; Jagannadham, Jaisri; Jaiswal, Sarika; Prabha, Ratna; Rai, Anil; Kumar, Dinesh (Frontiers in Microbiology, 2022)
Agricultural productivity is highly influenced by its associated microbial community. With advancements in omics technology, metagenomics is known to play a vital role in microbial world studies by unlocking uncultured microbial population present in the environment. Metagenomics is a diagnostic tool to target unique signature loci of plant and animal pathogens as well as beneficial microorganisms from samples. Here, we reviewed various aspects of metagenomics from experimental methods to techniques used for sequencing, diversified computational resources including databases and software tools. Exhaustive focus and study is conducted on the application of metagenomics in agriculture, deciphering various areas, including pathogen and plant disease identification, disease resistance breeding, plant pest control, weed management, abiotic stress management, post-harvest management, discoveries in agriculture, source of novel molecules/compounds, biosurfactants and natural product, identification of biosynthetic molecules, use in genetically modified crops and antibiotic resistant genes. Metagenomics wide association studies study in agriculture on crop productivity rates, intercropping analysis and agronomic field is analyzed. This article is a first of its comprehensive study and prospects from agriculture perspective, focusing on a wider range of applications of metagenomics and its association studies.